Le Musée archéologique de la faculté des lettres de Bordeaux (1886) - Marion Lagrange; Florent Miane (In Situ)
Founded in 1886, the Archaeological Museum of the Faculty of Letters in Bordeaux is the most visible manifestation of the new perception of sculpture and antique architecture by Archaeologists and, largely, of the transformation of university teaching at the end of the 19th century. The "rediscovery" of this museum is the opportunity to return to the genesis of the university collections and to deliver an initial analysis of existing funds today.